MutMap‐Gap: whole‐genome resequencing of mutant F2 progeny bulk combined with de novo assembly of gap regions identifies the rice blast resistance gene Pii. Issue 1 (24th June 2013) - Takagi, Hiroki; Uemura, Aiko; Yaegashi, Hiroki; Tamiru, Muluneh; Abe, Akira; Mitsuoka, Chikako; Utsushi, Hiroe; Natsume, Satoshi; Kanzaki, Hiroyuki; Matsumura, Hideo; Saitoh, Hiromasa; Yoshida, Kentaro; et al.
Summary: Next‐generation sequencing allows the identification of mutations responsible for mutant phenotypes by whole‐genome resequencing and alignment to a reference genome. However, when the resequenced cultivar/line displays significant structural variation from the reference genome, mutations in the genome regions missing from the reference (gaps) cannot be identified by simple alignment. Here we report on a method called 'MutMap‐Gap', which involves delineating a candidate region harboring a mutation of interest using the recently reported MutMap method, followed by de novo assembly, alignment, and identification of the mutation within genome gaps. We applied MutMap‐Gap to isolate the blast resistant gene Pii from the rice cv Hitomebore using mutant lines that have lost Pii function. MutMap‐Gap should prove useful for cloning genes that exhibit significant structural variations such as disease resistance genes of the nucleotide‐binding site‐leucine rich repeat (NBS‐LRR) class.